Evolutionary biology : a plant perspective - Cruzan, Mitchell B. (Oxford University Press, 2018)
Many characteristics that distinguish plants can be traced to their bacterial origin early in the history of life. The goal of this book is to develop an understanding of the origins and evolutionary implications of features unique to plants.